Creating Worlds that Create Audiences: Theorising Personal Data Markets in the Age of Communicative Capitalism - Vassilis Charitsis; Detlev Zwick; Alan Bradshaw (tripleC: Communication, Capitalism & Critique)
In this article, we draw on theories of biopolitical marketing to explore claims that personal data markets are contextualised by what Shoshana Zuboff calls “surveillance capitalism” and Jodi Dean calls “communicative capitalism”. Surveillance and communicative capitalism are characterised by a logic of accumulation based on networked captures of life that enable complex and incomprehensive processes of extraction, commodification, and control. Echoing recent theorisations of data (as) derivatives, Zuboff’s key claim about surveillance capitalism is that data representations open up opportunities for the enhanced market control of life through the algorithmic monitoring, prediction and modification of human behaviour. A Marxist critique, focusing largely on the exploitative nature of corporate data capitalism, has already been articulated. In this article, we focus on the increasingly popular market-libertarian critique that proposes individual control, ownership, and ability to commodify one’s personal data as an answer to corporate data extraction, derivation and exploitation schemes. We critique the claims that personal data markets counterbalance corporate digital capitalism on two grounds. First, these markets do not work economically and therefore are unable to address the exploitative aspect of surveillance capitalism. Second, the notion of personal data markets functions ideologically because it reduces the critique of surveillance capitalism to the exploitation of consumers and conceals the real objective of data capitalists such as Google, Facebook, Amazon and Apple to not (just) exploit audiences but to create worlds that create audiences.